Ultrasonic Echosignal Applied to Human Skin Lesions Characterization - Hanna PIOTRZKOWSKA; Jerzy LITNIEWSKI; Elżbieta SZYMAŃSKA; Andrzej NOWICKI (Archives of Acoustics, 2013)
The paper presents a classification of the healthy skin and the skin lesions (basal cell carcinoma) basing on a statistics of the envelope of ultrasonic echoes. The echoes envelopes distributions were modeled using Rayleigh and K-distribution. The distributions were compared with empirical data to find which of them better models the statistics of the echo-signal obtained from the human skin. The results indicated that the K-distribution provides a better fit. Also, a characteristic parameter of the K-distribution, the effective number of scatterers (M), was investigated. The values of the M parameter, obtained for the skin cancer (basal cell carcinoma), were lower as compared to those obtained for the healthy skin. The results indicate that the statistical quan- titative ultrasound parameters have a potential for extracting information useful for characterization of the skin condition.